PERENCANAAN,PENGAWASAN DAN EVALUASI SISTEM KENDALI PELAKSANAAN PROYEK BERBASIS PROTOKOL KESEHATAN COVID-19 BAGI TENAGA PROYEK DI DESA MEDANG, TANGERANG - Nadia Diandra; Mulyadi Sugih Dharsono; Stephen Valentino (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2022)
COVID-19 is a disease caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). COVID-19 can cause respiratory system disorders, ranging from mild symptoms such as flu to lung infections, such as pneumonia. To find out about the implementation of the COVID-19 Health protocol-based project for project workers in Desa Medang, Curug, Tangerang, it is necessary to directly supervise project personnel. The method used in the implementation of this community service activity is to identify, observe and study the construction process and the interactions of construction workers during the construction process by interviewing workers, especially field supervisors in Desa Medang, Curug, Tangerang regarding the COVID-19 Health protocol. Where it is hoped that direct interaction with construction workers can improve the project implementation control system based on the COVID-19 health protocol for project workers sustainably. The result of Community Service activities is the increased awareness of project workers in implementing the COVID-19 Health protocol, as well as the implementation of comprehensive Health protocol activities under established regulations. Keywords: COVID-19, Labor, Health Protocol